Quantitative lipidomic analysis reveals distinct metabolic traits between stromal cell subpopulations in human orbital adipose tissue - Shuwei Tian; Xiaoli Zhang; Jiayong Yu; Juan Cai; Danni Wei; Siqi Li; Pengfei Cai; Wei Song; Suihan Feng; Mengle Shao; Haizhou Li (Metabolism Open, 2025)
Adipose tissue, a pivotal metabolic regulator, houses diverse stromal cell populations influencing its dynamic functions. Recent omics studies, including transcriptomics and proteomics, have revealed intricate cellular heterogeneity, yet comprehensive metabolic profiling remains limited. Leveraging fluorescence-activated cell sorting (FACS), we isolated PDGFRα+ DPP4+ and PDGFRα+ DPP4- adipose stromal cells (ASCs) from human orbital adipose tissue (OAT). Integrating gene expression analysis, in vitro adipogenesis assays, and quantitative lipidomics, we characterized their functional and metabolic distinctions. DPP4- ASCs exhibited enhanced adipogenic potential and distinct lipidomic profiles, featuring elevated ceramides and triacylglycerols compared to DPP4+ ASCs. Differential gene expression highlighted metabolic and adipogenic gene signatures reflective of their functional roles in adipose tissue remodeling. Our findings underscore the metabolic heterogeneity within OAT stromal fibroblasts, implicating DPP4- ASCs as potent regulators of adipogenesis and metabolic homeostasis. These insights enhance our understanding of adipose tissue plasticity and may inform therapeutic strategies for conditions like thyroid-associated ophthalmopathy.